Perancangan Antarmuka Pengguna Aplikasi Pemasaran Namiroh berbasis Web dengan Metode Design Thinking PT. An Namiroh Travelindo - Deflion Yussac Sahlan; Fatwa Ramdani; Hanifah Muslimah Az-Zahra (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2022)
PT. An Namiroh Travelindo is a travel service company for Umrah and Hajj services plus which has branches in several major cities in Indonesia. However, PT. An Namiroh Travelindo experienced internal and external problems in business processes that arose due to the presence of the Covid-19 virus in Indonesia. The traditional system of business processes causes misunderstandings between leaders and agents to cause problems in the marketing process. Based on the problems above, the researcher wants to provide a modern business process solution by designing the user interface of the web-based namiroh marketing application that will utilize the design thinking method for the user interface design process. So with the creation of this application, agents can see the commission correctly and make it easier for the public to register and buy hajj and umrah packages at PT. An Namiroh Travelindo. This application design process uses the design thinking method that uses five stages, namely the empathy phase, define phase, ideate phase, prototype phase, and test phase. This study uses a usability scale system for usability testing with a task scenario that will achieve aspects of satisfaction, learnability, and efficiency. Based on the test results obtained a value of 83.5 so it can be concluded that the user interface design of the namiroh marketing application has a high level of satisfaction based on the data obtained. Based on the criteria for high acceptance, ranking (grade scale) above average, and good adjective ratings.